PENGARUH SIKAP DAN PERAN ORANG TUA TERHADAP PERGESERAN BAHASA LUWU DI KALANGAN ANAK-ANAK PADA MASYARAKAT LUWU KOTA PALOPO - Djamareng, Jumhariah; Jufriadi, Jufriadi (IAIN Palopo, 2016)
Abstract:This study aims to describe the condition of Luwu language shift among children in Palopo city.Furthermore, it was seen whether the attitude factor and the role of parents affect the use ofLuwunese. To answer these issues, the researchers involved the societies of Palopo who live inthe districts of Wara, East Wara, Bara, and Tellu Wanua as the population of this study. Then,this study involved 120 samples consisting of; 1) 60 children around 6 â 12-year-old (primaryschool age) in which ten children were chosen from each district; and 2) 60 older people (30-50Years old, married). Data collecting techniques were in forms of observation, questionnaires,and interviews through note taking and recording as the research instruments. The findingsshowed that the language shift occurred among children in Palopo city based on the datapercentage analysis obtained from the questionnaires. The use of Luwunese by parents was theroles of parents in providing significant influences on the language shift occurring in childrenshown by the percentage calculation where almost the respondents showed a lack of Luwuneseuse by children and parents in their family interactions. The parentsâ positive attitude towardsthe use of Luwunese indicated by the questionnaire percentage had no impact on Luwunesepreservation; whereas, the Luwunese shift occurred in Palopo city.